Asimilasi Bahasa dan Budaya Arab dalam Masyarakat Muslim Indonesia: Kajian Sosiolinguistik - Aziz, Althaf Javid H.; Butsainah, Ronaa Fitri; Erlina, Erlina; Koderi, Koderi; Rafli, Zainal; Ibrahim Khedr, Tamer Saad (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study examines the assimilation of the Arabic language and Arab-Islamic cultural elements within Indonesian Muslim society through a sociolinguistic perspective. Arabic has played a central role in shaping religious identity across the archipelago due to its position as the language of the Qur'an, Hadith, and Islamic scholarship. Using a library research method, this paper analyzes 20 international scholarly journals related to language contact, linguistic borrowing, religious sociolinguistics, and cultural globalization in Muslim-majority societies. The findings indicate that assimilation occurs at the lexical, phonological, semantic, pragmatic, symbolic, ritual, and institutional levels. Arabic loanwords dominate religious discourse, whereas cultural practices such as dress, religious rituals, honorific titles, and educational traditions reflect continuous integration with local Indonesian customs. Sociolinguistically, Arabic functions as a marker of piety, identity, and group solidarity reinforced by religious practices, Islamic education, transnational Islamic movements, and digital media. This study concludes that the assimilation of Arabic language and culture is a dynamic and ongoing process deeply embedded in Indonesian Muslim identity and social life.